PENGARUH CITRA TOKO TERHADAP KEPUTUSAN PEMBELIAN PADA AMANAH SWALAYAN RENGEL - IRAWATI, WINAIKA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The emergence of modern retail stores and consumer demand for convenient shopping place so that the emerging trading company engaged in retail trade in the form of mini- and self-service. Changes in consumer behavior in rural districts who began modern Rengel where a person in day-to-day needs like shopping in stores that started the modern retail. This study aims to determine the effect of store image on purchase decisions in supermarkets Rengel mandate where the independent variable is the location of the store (X1), product (X2), price (X3), services (X4), and physical facilities ( X) and the dependent variable is purchasing decisions (Y). Based on statistical data analysis , the indicators in this study are valid and variables are reliable. The results of the regression indicate that the store image simultaneously significantly influence purchasing decisions, the value of F at 39.814. In the classical assumption test, regression models multikolonieritas free, heterosdastisitas not happen, and the normal distribution. Partially, the variable that has the most impact is variable store locations with a significance level of 0.000. Figures Adjusted R Square of 0,494 = 49,4 % indicates that the variable location of the store (X1), product (X2), price (X3), services (X4), and physical facilities (X5) jointly to the purchasing decision variable is equal to 49,4 %. While the remaining 50,6 % is influenced by other variables outside the model of this study. Keywords: store image , purchasing decisions